2018
DOI: 10.1002/cld.783
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hepatitis C

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/12-5-reading-gordon a video presentation of this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 17 publications
0
23
0
3
Order By: Relevance
“…This burden is especially high among younger people who inject drugs, with up to 70% of new HCV infections occurring among people who inject drugs in the USA [ 4 ]. The number of new cases of HCV infection among this demographic has increased from 10,000 annually in 2005 to 40,000 annually in 2016 [ 5 ]. Owing to these increases in HCV infections among younger individuals, the Centers for Disease Control and Prevention (CDC), the US Preventive Services Task Force (USPTF), and the American Association for the Study of Liver Diseases–Infectious Diseases Society of America (AASLD–IDSA) have all endorsed universal screening for HCV in adults (≥18 years of age) [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This burden is especially high among younger people who inject drugs, with up to 70% of new HCV infections occurring among people who inject drugs in the USA [ 4 ]. The number of new cases of HCV infection among this demographic has increased from 10,000 annually in 2005 to 40,000 annually in 2016 [ 5 ]. Owing to these increases in HCV infections among younger individuals, the Centers for Disease Control and Prevention (CDC), the US Preventive Services Task Force (USPTF), and the American Association for the Study of Liver Diseases–Infectious Diseases Society of America (AASLD–IDSA) have all endorsed universal screening for HCV in adults (≥18 years of age) [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic infection with hepatitis C virus (HCV) is a public health concern in the world, which can lead to liver cirrhosis, and/or hepatocellular carcinoma (primary liver cancer) ( Jafri and Gordan, 2018 ). In 2002, National Institutes of Health Consensus Development Conference Statement reported more than 184 million persons had HCV infection ( National Institutes of Health Consensus Development Conference Statement: management of hepatitis C 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Every year three to four million people are newly infected and approximately 350,000 deaths occur ( Mohd et al, 2013 ). HCV demonstrates great genetic diversity with seven genotypes and at least 67 subtypes ( Jafri and Gordan, 2018 ). Overall, genotype 1 dominates with 44% of infections, followed by genotype 3 (25%) and 4 (15%) ( Polaris Observatory HCV Collaborators, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Globally, the infection rate of hepatitis C virus is ∼3%, with 184 million cases, and ∼399 thousand people die of hepatitis C every year. [ 3 5 ] The prevalence of hepatitis C is 2.8%, while the viraemic rate is 63.6% in China (including Taiwan). [ 6 , 7 ] Previous studies have reported that the widespread incidence of hepatitis C is related to blood transfusion and injection drug abuse, and the incidence of hepatitis C caused by opioid abuse is also on the rise.…”
Section: Introductionmentioning
confidence: 99%